Experimental Study of the Effect of Ultrasound on the Freezing Process of Bo Chinh Ginseng - Minh-Hieu Ngo; Hay Nguyen; The-Bao Nguyen; Thanh-Dat Le; Quang-Huy Le (Applied Sciences, 2022)
The main purpose of this study was to select the appropriate ultrasound parameters that support the freezing process of Bo Chinh ginseng. This process involves placing Bo Chinh ginseng in an open-air environment and ensuring that the transducer does not come into contact with the material. The research results show that the ultrasound power, ultrasound irradiation temperature and intermittency ratio all affect the freezing time, nucleation temperature, color and microstructure of the materials. When the ultrasound continuously operated during the freezing process, at a frequency of 20 kHz, there was a 29.1% reduction in the freezing time at a power level of 100 W as compared to freezing without the help of ultrasound irradiation. The irradiation temperature and nucleation temperature have a linear relationship (<semantics>y=−0.35x−0.93</semantics>) which can help to control the nucleation temperature, thereby changing the ice crystal size. Ultrasound-assisted freezing at a 0.6 intermittency ratio had the shortest freezing time. The microstructure of the material changed after ultrasound-assisted freezing and many microchannels and holes were generated. When frozen at a wave rate of 0.4, the microchannels that were created in the material effectively supported the process of water drainage in the drying sublimation stage. At the same time, ultrasound irradiation did not affect the color of the post-freezing material when compared to the color of the frozen material that did not undergo ultrasound irradiation.